The intensification of coastal hypoxia off central Chile: Long term and high frequency variability - De La Maza, Lucas; Farías, Laura (Frontiers in Earth Science, 2023)
Hypoxia is a phenomenon where dissolved oxygen (DO) is reduced to levels that are low enough to strongly affect ecological and biogeochemical processes. This occurs within the continental shelf off central Chile (36°S), influenced by seasonal coastal upwelling (spring-summer). Monthly measurements of DO and other oceanographic variables in the water column (1997-2021) over the 92 m isobath along with high-resolution and near-surface observations (POSAR buoy), are analyzed to examine incidences of hypoxia and understand the physical and biogeochemical processes modulating DO vertical distribution and its temporal variability. On average, the percentage of the water column with DO levels below 89 (hypoxia) and 22 (severe hypoxia) µmol L-1 reaches 68% (i.e. hypoxic waters are found below 30m) and 44% (below 50m depth), respectively, but during the upwelling season, as much as 87% (below 12 m depth) and 81% (below 17 m depth) of the water column exhibits these levels. On the sub-seasonal scale during upwelling season six hypoxic events lasting at least 2 days occur at 10 m depth. There is a strong seasonal correlation between the volume of the seawater presenting hypoxia and upwelling favorable winds. Furthermore, there is a high DO interannual variability partially related to the El Niño Southern Oscillation (ENSO). Over two decades, it is estimated that DO concentration in surface and subsurface layers decreases (up to 21 µmol L-1 decade-1) as waters get colder (up to -0.29°C decade-1). Remarkably, the volume of hypoxic and severe hypoxic waters over the shelf has increased more than 2 times since 1997 and shows a significant positive correlation with the upwelling index. These preliminary findings indicate that the increase in local DO consumption is partially associated with upwelling intensification. Given the clear evidence of wind intensification in coastal upwelling ecosystems and thus the increase in hypoxic events, the coastal zone may be highly vulnerable to hypoxia, impacting biological resources and biogeochemical cycles